2006
DOI: 10.1002/cta.344
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of a preseizure state: non‐linear EEG analysis in epilepsy by Cellular Nonlinear Networks and Volterra systems

Abstract: SUMMARYIn this paper we present our work analysing electroencephalographic (EEG) signals for the detection of seizure precursors in epilepsy. Volterra systems and Cellular Nonlinear Networks are considered for a multidimensional signal analysis which is called the feature extraction problem throughout this contribution. Recent results obtained by applying a pattern detection algorithm and a non-linear prediction of brain electrical activity will be discussed in detail. The aim of this interdisciplinary project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…[6][7][8][9] Recent studies have shown that the approach of analyzing the dynamics of interacting complex systems with the nonlinear dynamics of interacting nonlinear elements can also be extended to the concepts of phase synchronization 10 and generalized synchronization.…”
Section: 2mentioning
confidence: 99%
“…[6][7][8][9] Recent studies have shown that the approach of analyzing the dynamics of interacting complex systems with the nonlinear dynamics of interacting nonlinear elements can also be extended to the concepts of phase synchronization 10 and generalized synchronization.…”
Section: 2mentioning
confidence: 99%
“…Numerous interdisciplinary investigations (e.g. [22][23][24][25][26][27]) aim at a better understanding of neural dynamics related to epileptic seizure generation; many of them using methods from signal processing, complex systems theory and system biology. Several publications indicate that a possible transition from interictal to ictal states might be detected 625 by a higher-dimensional analysis of brain electrical activity [28][29][30][31][32] but still seizures cannot be anticipated with necessary sensitivity and specificity.…”
Section: Cellular Nonlinear Networkmentioning
confidence: 99%
“…Previous studies [5], [6], [8]- [11], [13], [15], [16] have shown that interesting results are obtained by the application of algorithms based on Cellular Nonlinear Networks [2]- [4] and Volterra-Systems [14]. Especially, distinct changes of the relative mean square error prior to epileptic seizures could be observed in a EEG-signal [17] prediction.…”
Section: Introductionmentioning
confidence: 96%